2008
DOI: 10.1590/s1519-69842008000500010
|View full text |Cite
|
Sign up to set email alerts
|

The inverted trophic cascade in tropical plankton communities: impacts of exotic fish in the Middle Rio Doce lake district, Minas Gerais, Brazil

Abstract: The present study deals with the ecological impacts of the introduction of two alien species of piscivorous fish in several lakes of the Middle Rio Doce lake district in Minas Gerais, Brazil. It was demonstrated that these effects were not restricted only to the fish community. The introduction of the predatory red piranha Pygocentrus nattereri and the tucunaré Cichla cf. ocellaris caused not only a sharp decrease in the number of native fish species, but also major shifts in other trophic levels. Just after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…Introduced piscivorous fishes, such as the Piranha Pygocentrus nattereri and the Tucunaré Cichla spp., can exert different pressures on the zooplankton: directly predating as larvae, and indirectly by disrupting other links of the food chain. However, predation by larvae in the limnetic zone is highly unlikely, since the larvae are much more numerous near-shore., In a study on the lakes of the middle River Doce valley, Pinto-Coelho et al (2008) observed an increase in Chaoborus density caused by the introduction of exotic piscivorous fish species into the lakes. According to the authors, the introduction of these species led to the collapse of the native planktivorous fish species and to the reduction of predation pressure on invertebrates, causing an increase in their density and, thus, an increase in the pressure on other zooplankton organisms by chaoborids.…”
Section: Discussionmentioning
confidence: 99%
“…Introduced piscivorous fishes, such as the Piranha Pygocentrus nattereri and the Tucunaré Cichla spp., can exert different pressures on the zooplankton: directly predating as larvae, and indirectly by disrupting other links of the food chain. However, predation by larvae in the limnetic zone is highly unlikely, since the larvae are much more numerous near-shore., In a study on the lakes of the middle River Doce valley, Pinto-Coelho et al (2008) observed an increase in Chaoborus density caused by the introduction of exotic piscivorous fish species into the lakes. According to the authors, the introduction of these species led to the collapse of the native planktivorous fish species and to the reduction of predation pressure on invertebrates, causing an increase in their density and, thus, an increase in the pressure on other zooplankton organisms by chaoborids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, young and smallsized fish species that could potentially exploit zooplankton are mostly associated with the littoral zone in warm lakes (Fernando, 1994;Arcifa and Northcote, 1997;Meschiatti and Arcifa, 2002;Agostinho et al, 2003;Teixeira-de Mello et al, 2009), and are, therefore, segregated from the limnetic zooplankton. Predatory invertebrates can exert greater pressure on zooplankton if they are not strongly controlled by fish (Lampert and Sommer, 2007;Pinto-Coelho et al, 2008). However, when other factors, such as turbidity and dissolved oxygen, reduce the spatial overlap between fish and Chaoborus, prey consumption by the dipteran larvae can exceed that of fish, becoming the major predatory force even when planktivores are abundant (Liljendahl-Nurminen et al, 2003).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…In 2005 an extensive survey indicated that invasive species had found their way to 90% of the lakes in the rio Doce State Park (Latini, 2005). As a long term-effect, exotics have apparently caused inverted cascade processes that affect the lowest trophic levels (Pinto-Coelho et al, 2008).…”
Section: Introductionmentioning
confidence: 99%